High stocking density and food restriction have minimum impact on size dispersal of cultured Senegalese sole ( Solea senegalensis, Kaup 1858) juveniles. Evidence for individual growth being regulated by population structure - SALAS-LEITON, E; ANGUIS, V; RODRIGUEZ-RUA, A; CANAVATE, J. P (Aquacultural engineering, 2011)
► Knowledge afforded by this work about effects of high stocking density and food restriction on population growth depensation constitutes a novel finding for this species. ► We demonstrate that both rearing conditions have a minimum impact on size dispersal of captive groups of sole juveniles. ► An individual growth regulation by population structure is also confirmed. The individual growth being regulated by population structure was studied in cultured populations of Senegalese sole ( Solea senegalensis Kaup) juveniles. Soles constituting an initial population were individually tagged and their specific growth rates (SGR) registered after two months of growth. Fish were then graded in order to achieve four new subpopulations based in their previous growths and cultured for other additional 60 days. Three subpopulations consisted of individuals that had previously shown an average SGR (% day −1) of 1.04 ± 0.3, 0.66 ± 0.1 and 0.18 ± 0.1, respectively. A fourth sole subpopulation was established from randomly selected juveniles to constitute the ungraded control group. Growth of the three subpopulations originally graded according to high (1.04% day −1), medium (0.66% day −1) and low (0.18% day −1) SGR soles, was always similar ( P > 0.05) at any time (close to 0.60% day −1). SGR distributions along time revealed a tendency of the three subpopulations to achieve similar growth rate dispersals to that of the ungraded group after 60 days of culture. The individual growth of sole juveniles was also determined in populations that were subject to increased stocking density and food restriction. Soles stocked at high density ( N = 110 fish tank −1; 30.97 ± 0.8 kg m −2) showed an increased growth standard deviation when compared with individuals kept at low density ( N = 20 fish tank −1; 6.20 ± 0.2 kg m −2). In contrast, it was found that population growth dispersal was unaffected in soles fed at a daily ration of either 0.25% or 1.0% of their biomass. Minimum consequences on overall size dispersal in terms of ΔCV were found when high stocking and restricted food ration conditions were compared to control groups. Overall results from this work indicate that individual growth of captive juvenile soles was mainly regulated at a population level, existing a strong tendency to achieve a social arrangement in terms of growth. High stocking density and low feeding ration assay suggests that potentially competitive rearing conditions do not contribute to increase population size dispersal during intensive production of S. senegalensis.